microRNAs and Cardiac Cell Fate - Chiara Piubelli; Viviana Meraviglia; Giulio Pompilio; Yuri D'Alessandra; Gualtiero I. Colombo; Alessandra Rossini (Cells, 2014)
The role of small, non-coding microRNAs (miRNAs) has recently emerged as fundamental in the regulation of the physiology of the cardiovascular system. Several specific miRNAs were found to be expressed in embryonic, postnatal, and adult cardiac tissues. In the present review, we will provide an overview about their role in controlling the different pathways regulating cell identity and fate determination. In particular, we will focus on the involvement of miRNAs in pluripotency determination and reprogramming, and specifically on cardiac lineage commitment and cell direct transdifferentiation into cardiomyocytes. The identification of cardiac-specific miRNAs and their targets provide new promising insights into the mechanisms that regulate cardiac development, function and dysfunction. Furthermore, due to their contribution in reprogramming, they could offer new opportunities for developing safe and efficient cell-based therapies for cardiovascular disorders.